Inheritance of Gending Sriwijaya Dance and Educative Values at Putri Rambut Selako Art Studio in Palembang City - Suryanti Retna Sari, Dyah; Hartono, Hartono; Triyanto, Triyanto (Catharsis, 2019)
Gending Sriwijaya Dance is a traditional dance in the South Sumatra region that has potential forms and values ​​that need to be preserved and inherited, art education at the studio is an effort to inherit traditional dance as practiced by the Putri Rambut Selako Art Studio. The purpose of this study is to describe and analyze the inheritance of the Gending Sriwijaya Dance through traditional dance education at the Putri Rambut Selako Art Studio. This research method uses a qualitative approach, with case study design, data validity technique with triangulation and data analysis procedures carried out through the stages of reduction, data presentation, and drawing conclusions. The results of this study indicate that dance learning in the studio becomes an effort to inherit the Gending Sriwijaya Dance which includes two aspects of inheritance, namely the learning process as enculturation and staging as a socialization activity and supported by potential environmental aspects of students, aspects of the teacher (trainer) method and evaluation of learning to achieve goals education as a process of inheritance, then there are values ​​inherited from students through traditional arts education at the Putri Rambut Selako Art Studio which researchers classified into three, among others: 1) Knowledge Value; 2) Attitude Value; 3) Skill Value. The benefit and contribution of this research is that the existence of dance education at the Putri Rambut Selako Art Studio can be a reference for other traditional art inheritance efforts through art education.